Wingless Flight : The Lifting Body Story - Reed, R. Dale, 1930-; Lister, Darlene, 1945- (Book collections on Project MUSE., 2015)
Most lifting bodies, or "flying bathtubs" as they were called, were so ugly only an engineer could love them, and yet, what an elegant way to keep wings from burning off in supersonic flight between Earth and orbit. Working in their spare time (because they couldn't initially get offical permission), Dale Reed and his team of engineers demonstrated the potential of the design that led to the space shuttle. This volume takes the reader behind the scenes with a blend of technical information and detail. The flying bathtub, itself, is finding new life as the proposed escape-pod for the Space Station.